Life cycle assessment for the determination of key environmental impact indicators in soilless tomato culture and mitigation potential - Litskas, Vassilis D.; Stavrinides, Menelaos; Economakis, Costas D.; Tzortzakis, Nikos G. (My University, 2021)
The interest in the use of mixtures of inorganic and organic materials as substrate media in soilless culture in greenhouses is increasing in parts of the world where the mixtures have not been used in common practice. Material efficacy can affect the plant yield, water and fertilizer use efficiency, energy consumption, and final cost for the production of 1 kg of produce. In this study, tomato plants (Solanum lycopersicum 'Belladona') were grown over five months in a closed soilless culture system on seven different substrates (perlite or pumice and their mixtures with 25 or 50% shredded maize stems) in an unheated greenhouse. Life cycle assessment was applied to assess the impact of the production system on the environment. As key performance indicators, the carbon footprint, the water footprint and energy efficiency were determined for the seven different substrates. The system boundaries were from cradle to farm gate. Comparisons of the indicators to greenhouse and field tomato production were made as well as suggestions to mitigate the impact of this production method on the environment.
Keywords: Carbon footprint; Energy intensity; Environmental performance; Substrates; Water use efficiency; Yield